A Configuration of Ultra-Wideband Planar Antenna Comprises Band Suppression at 5~6 and 3.3~3.7GHz - Jainal, Siti Fatimah; Mohamed, Norliza; Hamzah, Azura; Mohd Sam, Suriani (International Journal of Integrated Engineering, 2018)
Two-slits in a UWB planar antenna in the means of suppressing the frequency bandwidths for 5~6 and 3.3~3.7GHz are studied. Frequency bandwidths for 5~6 and 3.3~3.7GHz are known as the Wireless Local Area Network (WLAN) and Worldwide Interoperable for Microwave Access (WIMAX), respectively. Both are coexisted with the UWB frequency bandwidth that is allocated between 3.1 and 10.6GHz. Coexistence between these frequency bandwidths have potentially caused interferences such as signal disruption and data lost in the respective systems. Two-slits are etched in the conductor elements in the means of generating the notched-band characteristics by producing impedance mismatched in the proposed antenna. Band notching are generated for the frequency bandwidths 5~6G and 3.3~3.7GHz, respectively. Band notch peaks are desired to achieve higher than -5dB. Slits are etched in the elliptical element and ground plane for band notching at the frequency 5~6 and 3.3~3.7GHz, and optimized proposed antenna’s peak of the reflection coefficient S11 are given -3 and -4dB, respectively. Slits parameters are studied in order to recognize the dominant parameters that affect the notched-band characteristics. It is shown that the two-slits have engendered the notched-band characteristics in the UWB planar antenna and slits parameters could be exploited in order to influence the notched-band characteristics accordingly.